Analisis Penerapan Metode Lossy Pada Kompresi Citra Steganografi - Sembiring, Abdul Sani (MEANS (Media Informasi Analisa dan Sistem), 2018)
The internet has become a very important part of communication development in the world. Exchange of information over the internet has many advantages compared to other communication media, especially in terms of speed. But information sent via the internet, security cannot be accounted for. Tapping on confidential information, very often occurs in this communication media. Channels used by the internet are generally not safe channels. By using the lossy compression method, compression can only be applied to images that have similarities to themselves (self similiarity) so that the size of the image gets smaller and saves storage space and accelerates the sending of the image using internet media.